THE BLACKSMITH AND THE FARMER - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The development of small metal-working enterprises has become an important basis for agricultural mechanisation. Centered on the village blacksmith, they have shown great success in the cotton areas of southern Mali, in Borgou in Benin, and in...